2013
DOI: 10.1590/s0036-46652013000600006
|View full text |Cite
|
Sign up to set email alerts
|

Phlebotomine Sandflies in Rural Locations in the State of Parana, Southern Brazil

Abstract: SUMMARY This study reports the fauna and frequency of sandflies in domestic animal shelters, residences and other ecotopes in rural areas of the municipality of Bandeirantes, Paraná State. Sandflies were collected twice in eight rural villages by using Falcon traps from 8pm to 6am in 2008. In these localities 4,790 sandflies were collected, which were represented by ten sandfly species, prevailing of Nyssomyia neivai and Nyssomyia whitmani species. It was observed that animal shelters are the domestic ecotopes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…Most respondents reported that they lived near areas of vegetation ( p < 0.05), and it is known that environments with remnants of forest and fruit trees provide suitable breeding sites for sand flies because the insects feed on fallen fruits [ 17 , 18 ]. Thus, the presence of this type of vegetation around the homes of residents is a factor enabling the spread of the vector in these areas.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most respondents reported that they lived near areas of vegetation ( p < 0.05), and it is known that environments with remnants of forest and fruit trees provide suitable breeding sites for sand flies because the insects feed on fallen fruits [ 17 , 18 ]. Thus, the presence of this type of vegetation around the homes of residents is a factor enabling the spread of the vector in these areas.…”
Section: Resultsmentioning
confidence: 99%
“…The lack of sanitation in the study area is conducive to its maintenance as an environmental vector of VL because the garbage dumps and sewers exposed to the environment provide the type of organic matter that is a food source for immature and adult sand flies [ 17 , 18 ]. The presence of poor housing and environmental sanitation conditions are most likely associated with maintaining the endemicity of VL in these areas, given that the disease tends to affect disadvantaged populations [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, the presence of animal species different from rats was a protection factor against leishmaniosis in rats (OR= 0.01273 to 0.8341). A study on Nyssomyia neivai species broadly found in Paraná State (MEMBRIVE et al, 2004;DIAS-SVERSUTTI et al, 2007;SILVA et al, 2008;CERINO et al, 2009;CRUZ et al, 2013;MELO et al, 2013), performed in Ribeira Valley São Paulo State, examined 988 engorged females, and no rat blood was detected in the phlebotomines (MARASSÁ et al, 2013). According to Dias-Sversutti et al (2007), N. neivai and N. whitmani are opportunists and probably adjust their feeding habits based on the availability of hosts.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study (CARVALHO et al, 2014) using ecological niche modeling predicts southward expansion of L. flaviscutellata in South America because of climate change. Several studies have investigated phlebotomine fauna in Paraná State (GOMES & GALATI, 1977;TEODORO et al, 1993;TEODORO et al, 1999;OLIVEIRA et al, 2000;DIAS-SVERSUTTI et al, 2007;SILVA et al, 2008;CERINO et al, 2009;REIS et al, 2011;CRUZ et al, 2012;SANTOS et al, 2012;MEMBRIVE et al, 2012;CRUZ et al, 2013;MELO et al, 2013); none reported L. (L.) amazonensis vectors. Taking into account two autochthonous cases (one human and one canine) of leishmaniasis by L. (L.) amazonensis in North Paraná, more studies about phlebotomine fauna must be made in this region, now using Disney traps with rodents as baits (DORVAL et al, 2007), because L. flaviscutellata is strongly attracted to rodents (LAINSON & SHAW, 1968;SHAW & LAINSON, 1972;CARVALHO et al, 2014).…”
Section: Discussionmentioning
confidence: 99%